A COMPREHENSIVE APPROACH TO ASSESSING THE ECONOMIC, ENVIRONMENTAL, AND ORGANIZATIONAL-LEGAL SECURITY OF AGRIBUSINESS ENTITIES - BOHDANIUK, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is dedicated to the development of a comprehensive approach to assessing the economic, environmental, and organizational-legal security of agribusiness entities. The aim of the study is to analyze, systematize, and generalize the existing theoretical and methodological foundations of security for business entities and to develop a comprehensive approach to evaluating the economic, environmental, and organizational-legal security of agricultural enterprises. The article examines the importance of assessing the level of security in agribusiness as a key element of ensuring the efficiency, stability, and adaptability of enterprises operating in a complex and dynamic environment. A systemic approach to security evaluation is presented, which includes the analysis of economic, environmental, social, and technological aspects. It is revealed that agribusinesses face numerous challenges, such as economic uncertainty, climate change, market fluctuations, and technological innovations, requiring a comprehensive approach to identifying risks and developing appropriate response strategies. The need for integrating various security components into a unified system to ensure the resilience of agribusiness is substantiated. Key aspects of assessment are outlined, including economic security, environmental sustainability, and organizational-legal security. Economic security assessment involves analyzing financial indicators, capital stability, and resource use efficiency, enabling agricultural enterprises to optimize their operations and adapt to changing conditions. Environmental security is a crucial component for agribusiness, as enterprises are dependent on natural resources and face risks related to climate change. Evaluating environmental aspects, such as soil degradation, water scarcity, and CO2 emissions, helps develop sustainable farming practices, including the use of precision farming technologies. Organizational-legal security is also an important factor, as changes in legislation, new certification and licensing requirements, and other legal initiatives can significantly impact business operations. The research identified key vulnerabilities in agribusiness, particularly in financial, environmental, and organizational-legal aspects. A comprehensive approach to assessing the security level of agribusinesses is proposed, which includes multifactorial analysis, scenario modeling, and the use of digital technologies to improve forecast accuracy and management decision-making. Assessing compliance with economic, environmental, and organizational-legal security contributes to the strategic development of enterprises, allowing them to enhance their resilience to external challenges.